Effect of Arbuscular Mycorrhizal fungi and PGPR on heavy metal uptake by lady’s finger Ggrown on sewage sludge amended soil. - Othman, Radziah; Ishak, Che Fauziah; Azizan, Azizul Hafiz (2007)
A pot experiment was conductedto determine the effect of arbuscular mycorrhizal fungi (AMF) and a plant growth – promoting rhizobacteria (PGPR ) on the uptake of heavy metals by lady’s finger seedlings were grown in soil amended with 5 % (w / w ) sewage sludge.Glomus mosseae and Bacillus sphaericus UPM10 were inoculated individually or in combination to the respective pots. Plants inoculated with both mycorrhiza and bacteria had significantly higher shoot , root and fruit yields compared to the non-inoculated plants . Plant’s uptake of N and P was subsequently increased with microbial inoculation . In general , the uptake of heavy metals ( Cd , Pb , C u and Zn ) was higher in the plant shoots and root than in the fruits . Microbial inoculation had ni significant effect on heavy metals uptake expect for Zn. Highest Zn content was observed in the fruits of plants inoculated with both AMF and PGPR.High mycorrhizal root infection was observed in plants inoculated with AMF individually or in combination with UPMB10.